Pengembangan Buku Ajar Berbasis Keterampilan Berpikir Kritis - Salim Salim; Hendra Nelva Saputra (Universitas Muhammadiyah Sidoarjo, 2019)
This teaching material development offers a solution to facilitate the students ' critical thinking skills through chemical learning. The purpose of this research is to produce decent teaching materials to facilitate students' critical thinking skills. This type of research is development research using Dick, Carey, and Carey's development models. Research instruments use poll responses from learning media experts, learning design, and learning materials. The resulting development product is a teaching book. Based on the results of data analysis obtained from the responses of learning media experts, learning design experts, and learning materials experts demonstrate that the teaching materials are developed worthy to be used in the process of learning chemistry with the access The average percentage score amounted to 89.33% of the learning media experts, 83.33% of the learning design experts, and 93.33% of the learning material experts. This chemical teaching materials development product is also feasible to facilitate students ' critical thinking skills in the learning process. The results of the assessment of all test subjects against the critical Thinking skills indicator show an average percentage of 95% of the learning media experts, 80% of the learning design experts, and 100% of the learning material experts.